Bidirectional two-sample Mendelian randomization analysis investigates causal associations between cathepsins and inflammatory bowel disease - Wang, Na; Liu, Jun; Chai, Bao; Yao, Jianhong; Du, Xufang; Mei, Qi; Wang, Xuena (Frontiers in Genetics, 2024)
Background Cathepsins, key regulators of the pathology of gastrointestinal disorders such as inflammatory bowel disease (IBD), are a target protease that has attracted much attention in recent years. IBD is a chronic and relapsing inflammatory disorder of the gut. Traditional studies have shown a correlation between cathepsin and the risk of IBD, while the causal relationship remains unclear. Methods This study utilized Mendelian randomization techniques to evaluate the causal relationships between eleven cathepsins and the subtypes of IBD, such as ulcerative colitis (UC) and Crohn’s disease (CD). We also performed a series of sensitivity analyses to validate the primary Mendelian randomization (MR) results, including Cochran’s Q test, the MR-PRESSO global test, and the MR pleiotropy test. Results The forward MR analyses showed no significant association between cathepsins and IBD. Reverse Mendelian randomization analyses suggested that UC might lead to elevated cathepsin G levels [inverse-variance weighted (IVW): p = 0.038, b = 9.966], and CD might cause a decrease in cathepsin B levels [IVW: p = 0.002, b = −10.525] and cathepsin L1 levels [IVW: p = 0.045, b = −4.742]. Conclusions Our findings offer novel and comprehensive evidence on the impact of UC or CD on cathepsins, potentially providing valuable insights into the treatment and prognosis of IBD.